The Effect of Service Quality on Customer Trust With Customer Satisfaction As Intervening Variables in Home Care Health Service RawatDiRumah.Com - Nurzali, Edward; Sidharta, Helena (Review of Management and Entrepreneurship, 2023)
RawatDiRumah.com is a home care health service that is expected to make it easier for people to get medical services at home to reduce the risk of making contact with the diseases that may occur if they are treated at the hospital. Seeing the fairly high competition between home care health services, RawatDiRumah.com needs to pay attention to service quality which will affect customer satisfaction and customer trust. The purpose of this research is to determine the effect of service quality on customer trust through customer satisfaction as a mediating variable. The population of this research is all customers who have used the RawatDiRumah.com home care service at least 2 times from June - December 2021. The sample used in this research was 86 respondents who were determined by the saturated sample method. The model used by the researcher is a statistical analysis of Structural Equation Modeling (SEM) and analyzed using Partial Least Square (PLS). The results of this study indicate that there is a positive and significant influence between service quality and customer satisfaction, customer satisfaction and customer trust, service quality and customer trust, and customer satisfaction acts as a mediating variable in the relationship between service quality and customer trust. of home care health service RawatDiRumah.com. Keywords: home care; service quality; customer satisfaction; customer trust